Rešitev, ki je postala problem - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1997)
The existing political systems often prove unable to manage ethnic diversity and relations in plural societies. Furthermore, the existing concept of nation-states - still based on the presumption of ethnic homogeneity and ethnically defined national interests - could generate ethnic conflicts. There is a need to transform the existing concept of nation-states. The future development is difficult to predict. Nevertheless, in a way contradicting tendencies - decentralization, devolution, regionalization and federalization at the (sub)national level, cooperation and integration at the international level - seem to be main characteristics of this process. Hopefully these tendencies will lead to the concept of multinational state that will be perceived an ethnically friendly or at least neutral mechanism by all distinct communities.
Keywords: etnični pluralizem; nacionalna država; večkulturnost; večnacionalnost